'I had nothing. It's just life experience that helped me through that situation': Australian audiologists' perspectives on audiological clinical practice for traumatic brain injury and rehabilitation. (7th June 2022) - Šarkić, Bojana; Douglas, Jacinta. M.; Simpson, Andrea
ABSTRACT: Objective: Australian Audiologists' perspectives on standard non-specialized clinical practice in the context of Traumatic Brain Injury (TBI) were examined, including the perceived barriers to optimal service provision. Design: A qualitative research design utilizing semi-structured interviews was conducted using purposive sampling. Nine participants were interviewed about their understanding of the impact of TBI on hearing and balance; identification, diagnosis and management of auditory and vestibular dysfunction following TBI; barriers to service delivery; training relating to complex clients (i.e., TBI); and awareness of referral pathways. Results: Three major themes, each with subthemes, were evident in the data. The major themes reflected general considerations of audiological professional culture and specific issues related to knowledge of TBI and clinical practice with patients. Analysis revealed that professional culture seemed to act as a contextual barrier and interacted with the perceived lack of TBI related knowledge to hinder optimal clinical practice in this patient population. Conclusion: Application of the biopsychosocial model, including interdisciplinary care in the management of patients with TBI, is needed. An improvement in theoretical and practical knowledge encompassing the wide-ranging effects of TBI is critical for the optimal audiological service delivery.